Effect of 48-hour calf removal - Simms, D.D.; Odde, Kenneth G.; Corah, L.R. (Kansas State University. Agricultural Experiment Station, 2011)
In three field trials, we removed calves from 187 beef cows for 48 hours at the beginning of the breeding season to determine the effect on the cows' cycling activity, conception rate, and pregnancy rate. When calves were removed, the cows were injected with Lutalyse. Removing calves for 48 hours did not change weight gain or sickness incidence of calves, but neither did it facilitate the cows' rebreeding.
Keywords: Beef; Calf; Gain; Conception rate; Pregnancy rate